Desarrollo de la enseñanza de la guitarra clásica en Costa Rica de 1970 a 1996 - Barquero Moncada, Fabrizio (2009)
UCR::Docencia::Ciencias Sociales::Facultad de Educación::Escuela de Formación Docente